Relationship Between Histological Features of Non-alcoholic Fatty Liver Disease and Ectopic Fat on Magnetic Resonance Imaging in Children and Adolescents - Lee, Eun Hye; Kim, Ji Young; Yang, Hye Ran (Frontiers in Pediatrics, 2021)
Objectives: To investigate the association between ectopic fat content in the liver and pancreas, obesity-related metabolic components, and histological findings of non-alcoholic fatty liver disease (NAFLD) in children. Methods: This cross-sectional study investigated 63 children with biopsy-proven NAFLD who underwent magnetic resonance imaging (MRI), anthropometry, laboratory tests, and body composition analysis. Clinical and metabolic parameters, MRI-measured hepatic fat fraction (HFF) and pancreatic fat fraction (PFF), and histological findings were analyzed. Results: In a total of 63 children (48 boys, median age 12.6 years, median body mass index z-score 2.54), HFF was associated with histological steatosis (10.4%, 23.7%, and 31.1% in each steatosis grade, P < 0.001; Spearman’s rho coefficient [rs] = 0.676; P < 0.001) and NAFLD activity score (rs = 0.470, P < 0.001), but not with lobular inflammation, hepatocyte ballooning, and hepatic fibrosis. PFF was not associated with any histological features of the liver. Waist circumference-to-height ratio and body fat percentage were associated with the steatosis grade (P = 0.006 and P = 0.004, respectively). Alanine aminotransferase was not associated with steatosis but was associated with lobular inflammation (P = 0.008). Lobular inflammation was also associated with high total cholesterol and low-density lipoprotein cholesterol and metabolic syndrome (P = 0.015, P = 0.036, and P = 0.038, respectively). Conclusions: Hepatic steatosis on MRI was only associated with the histological steatosis grade, while elevated serum levels of liver enzymes and lipids were related to the severity of lobular inflammation. Therefore, MRI should be interpreted in conjunction with the anthropometric and laboratory findings in pediatric patients.